Alzheimer's Disease: Hematite‐Based Photoelectrode Materials for Photoelectrocatalytic Inhibition of Alzheimer's β‐Amyloid Self‐Assembly (Adv. Healthcare Mater. 8/2017). Issue 8 (19th April 2017) - Kim, Kayoung; Lee, Byung Il; Chung, You Jung; Choi, Woo Seok; Park, Chan Beum
Abstract : The self‐assembly of β‐amyloid peptides into aggregates is a major pathological hallmark of Alzheimer's disease that affects more than 11% of the population aged over 65. In article number1601133, Chan Beum Park and co‐workers show that β‐amyloid self‐assembly can be suppressed effectively via photoelectrocatalytic mechanism using a hematite‐based photoelectrode platform.